2023
DOI: 10.3390/ijms24065395
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid Self-Aggregation in Aqueous Media: A Long Journey toward the Definition of Structure–Property Relationships

Abstract: The need to protect human and environmental health and avoid the widespread use of substances obtained from nonrenewable sources is steering research toward the discovery and development of new molecules characterized by high biocompatibility and biodegradability. Due to their very widespread use, a class of substances for which this need is particularly urgent is that of surfactants. In this respect, an attractive and promising alternative to commonly used synthetic surfactants is represented by so-called bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 247 publications
0
2
0
Order By: Relevance
“…This is consistent with studies that have indicated that rhamnolipids self-assemble into various structures, including micelles, vesicles, lamellar structures, and even mesophases, depending on factors such as concentration, pH, temperature, presence of additives, and sample heterogeneity (congeners). (68,69) However, the micelles we have characterized here are distinctly smaller (~30 nm in diameter) than those previously characterized (~100-1000 nm). ( 70) This discrepancy may have been due to the different media used to grow the pathogen, the different methods for harvesting, and processing of the secreted products.…”
Section: Discussionmentioning
confidence: 57%
“…This is consistent with studies that have indicated that rhamnolipids self-assemble into various structures, including micelles, vesicles, lamellar structures, and even mesophases, depending on factors such as concentration, pH, temperature, presence of additives, and sample heterogeneity (congeners). (68,69) However, the micelles we have characterized here are distinctly smaller (~30 nm in diameter) than those previously characterized (~100-1000 nm). ( 70) This discrepancy may have been due to the different media used to grow the pathogen, the different methods for harvesting, and processing of the secreted products.…”
Section: Discussionmentioning
confidence: 57%
“…Biosurfactants, as an environmentally sustainable alternative to conventional surfactants, offer the potential to mitigate the environmental impact caused by the escalating production of industrial surfactant-containing formulations [1,2]. In recent years, heightened concern for environmental issues has directed scientific and technological research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…While canonical synthetic surfactants are classified based on their polar head properties, Rosenberg and Ron [31] introduced a classification method for biosurfactants that centers on their molecular weight. This classification system categorizes biosurfactants into two groups: low-molecular-weight (LMW) and high-molecular-weight (HMW) variants [2,6,28,[31][32][33][34]. LMW biosurfactants, which include glycolipids and lipopeptides, are known for their ability to reduce surface and interfacial tension while enhancing wetting abilities [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in 1995: acidic pH promotes the vesicle phase, while alkaline pH promotes the micellar phase. However, these and many other works, of which the self-assembly properties were just reviewed, were performed on sources of RLs containing both the di-rhamnolipid (RhaRhaC10C10) and monorhamnolipid (RhaC10C10), ,, thus precluding full understanding of the structure–property relationship. Studies concentrating on either mono- or di-RLs started with the work of Chen et al ., who showed that in buffer at pH 9, RhaRhaC10C10 tends to form micelles, while RhaC10C10 tends to form vesicles.…”
Section: Introductionmentioning
confidence: 99%